Human aspects of IT for the aged population. applications in health, assistance, and entertainment : 4th International Conference, ITAP 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: applications in health, assistance, and entertainment : 4th International Conference, ITAP 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available